Heart rate response to ultraendurance cycling. Issue 1 (1st February 2003) - Neumayr, G; Pfister, R; Mitterbauer, G; Gaenzer, H; Sturm, W; Hoertnagl, H
Abstract : The heart rate (HR) response to ultraendurance cycling is poorly understood. This case report describes the exercise intensity of ultraendurance cycling by means of HR monitoring in a well trained male amateur cyclist performing the Ötztal Radmarathon twice en bloque in a circuit of two identical laps (distance 460 km; cumulative altitude difference 11 000 m). The overall intensity was moderate (HRmean = 130 beats/min; HRmean /HRmax = 0.71) corresponding to an average individual workload of 47% of Vo 2 max . Almost the whole race was performed under aerobic conditions (99.6%); high intensity work was negligible (0.4%). The average speed and the HR response also declined in the course of the two laps, average speed by 17.2% (23.8 to 19.7 km/h), HRmean by 10.1% (138 to 124 beats/min), and HRmean /HRmax by 10.7% (0.75 to 0.67). This scale of HR decrease corresponds to comparable data gained in the field of triathlon and represents a specific cardiac feature of ultraendurance exercise in general.